The Role of networks in the internationalization process of Finnish design companies - Nikkinen, Essi (My University, 2014)
Finnish design has attracted global attention lately and companies within the industry have potential in international markets. Because networks have been found to be extremely helpful in a firm’s international business operations and usefulness of networks is not fully exploited, their role in Finnish design companies is investigated. Accordingly, this study concentrates on understanding the role of networks in the internationalization process of Finnish design companies. This was investigated through describing the internationalization process of Finnish design companies, analyzing what kind of networks are related to internationalization process of Finnish design companies, and analyzing how networks are utilized in the internationalization process of Finnish design companies. The theoretical framework explores the Finnish design industry, internationalization process and networks. The Finnish design industry is introduced in general and the concept of design is defined to refer to the industries of textiles, furniture, clothing, and lighting equipment in the research. The theories of internationalization process, the Uppsala model and Luostarinen’s operation modes, are explored in detail. The Born Global theory, which is a contrary view to stage models, is also discussed. The concept of network is investigated, networks are classified into business and social networks, and network approach to internationalization is discussed. The research is conducted empirically and the research method is a descriptive case study. In this study, four case companies are investigated: the interior decoration unit of L-Fashion Group, Globe Hope, Klo Design, and Melaja Ltd. Data is collected by semi-structured interviews and the analysis is done in the following way: the case companies are introduced, their internationalization processes and networks are described and, finally, the comparison of the case companies is done in a form of cross-case analysis. This research showed that cooperation with social networks, such as locals or employees who have experience from the target market can be extremely helpful in the beginning of a Finnish design company’s internationalization process. This study also indicated that public organizations do not necessarily enhance the internationalization process in a design company point-of-view. In addition, the research showed that there is cooperation between small Finnish design companies whereas large design companies are not as open to cooperation with competitors.